Improving MGMP teachers’ self-efficacy through technical guidance in learning from home program - Suryawati, Evi; Harfal, Zaldi; Syafrinal, S. (Universitas Muhammadiyah Malang, 2021)
The target of this technical guidance was secondary teachers of natural sciences, social sciences, and language who were members of the Teachers Professional Development Forum or Musyarawah Guru Mata Pelajaran (MGMP) in Siak Kecil, Bengkalis Regency. This training aimed to provide digital literacy strengthening for teachers in designing, implementing, and evaluating home-learning programs. This technical guidance was carried out through an online platform (Zoom) and offline mentoring in the MGMP discussion forum. The technical guidance mechanism consists of training and simulations in designing digital learning media in PowerPoint presentations, video monologues, e-student worksheets, and e-modules using software applications such as Filmora, Explee, Sigil, and Kinemaster. The results of this technical guidance were increasing self-efficacy with indicators of confidence in completing tasks (high), internal motivation (high), persistence (high), and being able to overcome obstacles and difficulties (high). There was also an increase in teachers' digital literacy in the aspects of data awareness (good), data analysis skills (sufficient), and ability to focus (excellent). The assessment of the results also showed that participants could design and use applications to carry out digital learning from home. Overall, this technical guidance positively impacted teachers' Continuing Professional Development (CPD), especially secondary teachers in Siak Kecil and Lubuk Dalam Sub-districts in Riau Province.